2021
DOI: 10.1177/03635465211059162
|View full text |Cite
|
Sign up to set email alerts
|

Does Transection of the Superficial MCL During HTO Result in Progressive Valgus Instability?

Abstract: Background: During high tibial osteotomy (HTO), the superficial medial collateral ligament (sMCL) is cut or released at any degree to expose the osteotomy site and achieve the targeted alignment correction according to the surgeon’s preference. However, it is still unclear whether transection of sMCL increases valgus laxity. Purpose: We aimed to assess the outcomes and safety of sMCL transection, especially focusing on iatrogenic valgus instability. Study Design: Case series; Level of evidence, 4. Methods: Sev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 59 publications
1
12
1
Order By: Relevance
“…Also, for the medial positioned plate, we should consider the more aggressive release of MCL [ 18 ]. There is still concern about the complete release of the superficial MCL, however, in a previously reported our study, the transection of the superficial MCL during MOWHTO does not increase valgus laxity [ 33 ].…”
Section: Discussionmentioning
confidence: 85%
“…Also, for the medial positioned plate, we should consider the more aggressive release of MCL [ 18 ]. There is still concern about the complete release of the superficial MCL, however, in a previously reported our study, the transection of the superficial MCL during MOWHTO does not increase valgus laxity [ 33 ].…”
Section: Discussionmentioning
confidence: 85%
“…Another possible reason is the combined cartilage procedure, which was performed in most of the patients in this study (84.1%). Several studies reported that an increase in the widening of the medial joint space may be associated with cartilage regeneration after HTO [43], although differing opinions persist [42, 44]. In our cohort of 104 consecutive patients who underwent HTO with a 3D‐printed gapper, only 63 (60.5%) were included based on the criteria for well‐performed bony correction.…”
Section: Discussionmentioning
confidence: 99%
“…Releasing or resecting the shallow layer of the MCL allows alignment to be corrected. 16 Yet, despite the advantages, many patients experience postoperative swelling and pain in the affected limb due to bleeding from the osteotomy site. There have also been cases reported in which excessive intraoperative release of the MCL has resulted in postoperative MCL insufficiency and external deformity due to altered collateral ligament balance.…”
Section: Discussionmentioning
confidence: 99%